Representation Of Feminism In Kretek Girl Serial Film Episode 2 - Yuliwar, Yohanes Sonnie; Harahap, Halomoan (UNIVERSITAS PAKUAN, 2024)
This study aims to analyze the representation of feminism in Gadis Kretek episode 2, focusing on how women are depicted through narrative, visuals, and dialogue. This study also explores whether female characters have full agency or are subject to the male gaze, and how social, cultural, and class factors influence these representations. In addition, this study compares the representation of feminism in Gadis Kretek with other films or series in Indonesia, and assesses its impact on audience perceptions of feminism and the role of women in Indonesia. The method used in this study is John Fiske's semiotic approach, which focuses on the analysis of signs in media texts, both in narrative and visual aspects. This method is integrated with feminist theory, especially the concept of the